'Being in your body' and 'being in the moment': the dancing body-subject and inhabited transcendence. Issue 1 (2nd January 2018) - Purser, Aimie C. E.
Abstract: Sports studies is currently dominated by the intellectualist approach to understanding skill and expertise, meaning that questions about the phenomenological nature of skilled performance in sport have generally been overshadowed by the emphasis on the cognitive. By contrast, this article responds to calls for a phenomenology of sporting embodiment by opening up a philosophical exploration of the nature of athletic being-in-the-world. In particular, the paper explores the conceptualisation of immanence and transcendence in relation to the embodied practice of dance, engaging with Merleau-Ponty's important insight that the body can be a source of transcendence. I also draw on data from in-depth qualitative interviews with professional contemporary dancers to explore dancers' concepts of 'being in your body' and 'being in the moment', and to suggest that during the actual embodied practice of dance, dancers do not experience transcendence and immanence as they are conceptualised in philosophy. Rather, I argue, dancers experience a third mode of being that is somehow in-between these two binary terms. I have called this 'inhabited transcendence'.